Toxic effects of ionic liquid 1-octyl-3-methylimidazolium bromide on the antioxidant defense system of freshwater planarian, Dugesia japonica. (September 2016) - Zhang, He-Cai; Shi, Chang-Ying; Sun, Li-Qun; Wang, Fan; Chen, Guang-Wen
The activities of antioxidant enzymes and the levels of glutathione (GSH) and malondialdehyde (MDA) were determined when freshwater planarian Dugesia japonica was exposed to different concentrations of 1-octyl-3-methylimidazolium bromide ([C8 mim]Br) for one, three, and five days. The results showed that superoxide dismutase (SOD) activity began to increase in all treated groups after three days of exposure, while catalase (CAT) activity was inhibited after the first day, but increased notably on the fifth day except for the lowest concentration group. The activity of glutathione peroxidase (GPX) was induced from the first day of exposure and increased significantly after five days in all treated groups. During the experiment, the levels of intracellular GSH in all treated groups were higher than that of the control group. Changes in MDA suggest that [C8 mim]Br is toxic to D . japonica and may result in lipid peroxidation in planarian. Our results also indicate that GPX as well as GSH seem to be more sensitive biomarkers of oxidative stress compared with SOD and CAT.